2021
DOI: 10.9734/ajaees/2021/v39i1030718
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Shrimp (Litopenaeus vannamei) in Nagapattinam District of Tamil Nadu

Abstract: Shrimp has become a popular seafood delicacy across the world. Shrimp is one of the widely traded seafood items and shrimp farming has created huge employment opportunities and gives foreign exchange to developing Nations. Shrimp exports have grown substantially with the introduction of Litopenaeus vannamei in India. The study analyses the economics of shrimp production and the constraints faced by the shrimp farmers in Nagapattinam district of Tamil Nadu. The economic analysis indicated that shrimp farmers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
6
1
Order By: Relevance
“…However, the results of the present study were different from what Rajarajan [17] and Narkis et al [18] reported. Rajarajan [17] reported that the shrimp farmers were mostly educated only up to middle school.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the results of the present study were different from what Rajarajan [17] and Narkis et al [18] reported. Rajarajan [17] reported that the shrimp farmers were mostly educated only up to middle school.…”
Section: Resultscontrasting
confidence: 99%
“…Rajarajan [17] found predominant age group of the shrimp farmers (50%) was between 36 and 45 years. Narkis et al [18] found that majority of shrimp farmers belonged to the middle age group. Umamaheswari et al [19] reported [21] and Umamaheswari et al [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the farmers were middle aged. In the study reported by Narkis et al [8] middle age group people were predominantly engaged in shrimp farming in Nagapattinam district of Tamil Nadu. Majority of the farmers had nuclear type families with higher secondary and graduate level education.…”
Section: Socio-economic Profile Of the Shrimp Culture Farmersmentioning
confidence: 92%